Factors Causing Incomplete Filling of Medical Resumes of Inpatients in Hospitals: Literature Review - Hendro Hendro; Ascobat Gani (PT Mattawang Mediatama Solution, 2023)
The medical resume or summary of the patient's history must be filled out completely, containing important information about the disease, examination and treatment provided with a standard of 100% completeness. Incomplete resumes will disrupt process continuity and patient safety. The aim of this research is to analyze the factors that cause incomplete filling out of medical resumes for inpatients in hospitals based on the management elements consisting of 5M, namely Man, Money, Method, Material, and Machine. The research method used is a literature review. Search articles using databases Google Scholar with selection according to inclusion and exclusion criteria. The number of literature found was 8 journals. The results obtained in this research are from the elements man limited number of human resources, high workload, time constraints, lack of understanding by officers regarding the importance of filling out resumes, and no training for officers. Element money, there are no constraints on funding sources. Element method namely lack of socialization of SOPs, SOPs do not yet exist, there is no system reward and punishment, SOP is not detailed enough, there is no evaluation of resume completeness. Element material, that is, the resume filling items are less simple. Element machine, namely inadequate facilities and infrastructure and slow distribution of files. The solutions taken to overcome this are calculating the amount of workload, implementing a disciplined attitude, providing training, preparing a special budget, creating and socializing SOPs, providing reward and punishment. redesigning resume forms, completing facilities and infrastructure in the medical records unit.